Development of a black pepper harvester - V Ganesan, K S K Aneeshya, G K Krishnanunni, (Journal of Spices and Aromatic Crops, 2013)
Three models of pepper harvester were fabricated and evaluated on the basis of efficiency in the cutting action and easiness in operation. All the three models basically consisted of a mild steel cutting unit, aluminium conveying pipe and a collecting basket. The main concepts adopted for the fabrication were impact, shear and pulling action for the proper insertion and cutting of the spikes and collection. The test was conducted for Panniyur variety out of which, the most efficient and user friendly was the second model due to its light weight, easiness in operation and minimum loss. The main advantages accounted for this model were simultaneous cutting and collection of spikes without heavy loss.